Serum levels of various vitamins in periodontal health and disease- a cross sectional study - Mayank Hans; Praveen Kumar Malik; Veenu Madaan Hans; Ashi Chug; Mayank Kumar (Elsevier, 2023)
Objectives: Vitamins are micronutrients that are required in small or trace amounts. They play an essential role in the metabolism and maintenance of tissue function. This investigation aimed to assess if a deficiency of certain essential vitamins is a risk factor for developing periodontitis. Methods: The subject population consisted of 100 subjects, 50 with generalized chronic periodontitis and 50 periodontally healthy volunteers. The following clinical parameters were measured: Gingival Index, pocket depth (mm); Clinical Attachment Loss (mm). Serum samples were collected and analyzed for levels of cis-β-carotene, β-cryptoxanthin, vitamin B 12, folate, vitamin D, and vitamin E. Individual data collected was summarized and analyzed using statistical software. Results: All the clinical parameters for periodontal status in the periodontitis group compared to healthy volunteers were highly significant (p < 0.0001). The mean levels of all the micronutrients, vitamin A precursors cis-β-carotene and β-cryptoxanthin, folate, vitamin B 12, D & E were lower in the periodontitis group than the healthy volunteers, although the difference was statistically significant only in case of β-cryptoxanthin, Vitamin B12 and Vitamin D (p < 0.05). Conclusions: The findings of our study suggest that serum micronutrient levels especially Vitamin A, Vitamin B 12, and Vitamin D may be modifiable risk factors for periodontal disease. Providing an optimized combination of various vitamins in each meal in combination with sufficient measures of standard oral hygiene care may provide an important role in the prevention of periodontitis.